Homeland and exile : biblical and ancient Near Eastern studies in honour of Bustenay Oded - Oded, Bustenay.; Galil, Gershon.; Geller, Mark, Ph. D.; Millard, A. R. (Vetus Testamentum, Supplements, 2009)
This volume is a scholarly tribute to Bustenay Oded's distinguished career from some of the many contemporaries, colleagues, and former students who not only admire, and keep being inspired by his achievements, but who also count him as a friend. The title points to the remarkable span of Bustenay Oded 's research and research interests. Accordingly, the Festschrift's thirty original contributions deal with a wide range of topics, focusing on the Assyrian Empire, as well as on the Hebrew Bible and other cultural contents.